2018
DOI: 10.1161/jaha.118.009775
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Dysfunction in the Sigma 1 Receptor Knockout Mouse Associated With Impaired Mitochondrial Dynamics and Bioenergetics

Abstract: Background The Sigma 1 receptor (Sigmar1) functions as an interorganelle signaling molecule and elicits cytoprotective functions. The presence of Sigmar1 in the heart was first reported on the basis of a ligand‐binding assay, and all studies to date have been limited to pharmacological approaches using less‐selective ligands for Sigmar1. However, the physiological function of cardiac Sigmar1 remains unknown. We investigated the physiological function of Sigmar1 in regulating cardiac hemodynamics u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 88 publications
3
74
0
Order By: Relevance
“…Following 4 weeks of "binge and crash" METH administration, we assessed the cardiac dimensions and function using M-mode echocardiography (Fig. 3) 32,[35][36][37][38] . Cardiac systolic parameters, i.e., percent fractional shortening (%FS) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following 4 weeks of "binge and crash" METH administration, we assessed the cardiac dimensions and function using M-mode echocardiography (Fig. 3) 32,[35][36][37][38] . Cardiac systolic parameters, i.e., percent fractional shortening (%FS) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, activation of Sigmar1 using the Sigmar1 agonist PRE-084 has been shown to limit METHinduced dopamine efflux in dopaminergic neurons, attenuate METH-induced locomotion, and motivate behavior and the drug-seeking brain reward function 29 . We have previously reported that Sigmar1 is highly expressed in the heart 30,31 , and that the genetic loss of Sigmar1 causes altered cardiac mitochondrial morphology and dysfunction, leading to cardiac contractile dysfunction 32 . Despite all these studies suggesting Sigmar1's potential role in cardiac physiology and also serve as a direct target of METH, to our knowledge, no studies to date explored the direct involvement of Sigmar1 in the development of METH-associated cardiac pathology.…”
mentioning
confidence: 99%
“…It is worth mentioning that deacetylation of OPA1-but not of other mitochondrial proteins including SOD2-maintained in the long term in Sirt3 -/animals, corrected cardiac dysfunction and fibrosis, demonstrating this maneuvre's previously unanticipated potential for cardiac protection. Studies have shown that mitochondrial dysfunction in cardiomyocytes critically contributes to the development of age-associated cardiac fibrosis by impairing bioenergetics and reducing cell survival (1,28,49). Furthermore, based on the recent evidence that Complex I inhibition is sufficient to promote the development of fibrosis in the lung, it is tempting to infer that the normalization of Complex I activity through mutOpa1 gene transfer contributes to the amelioration of cardiac fibrosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have also identified several molecular chaperones, including calnexin [ 108 ], syntaxin-17 and sigma-1 receptor (Sig-1R) at MAMs, which are involved in the regulation of information exchange, such as Ca 2+ ions between the ER and mitochondria. Sig-1R is a chaperone located in MAMs that regulates Ca 2+ transfer between mitochondria and ER by binding with IP3R3 [ 109 ]. Upon the induction of ER stress, Sig-1R is separated from BIP, and IP3R3 is stabilized to accelerate Ca 2+ influx from the ER into mitochondria to increase the production of ATP.…”
Section: Maintenance Of Mitochondrial Ca 2+ Homeosmentioning
confidence: 99%
“…Upon the induction of ER stress, Sig-1R is separated from BIP, and IP3R3 is stabilized to accelerate Ca 2+ influx from the ER into mitochondria to increase the production of ATP. It has been suggested that Sig-1R knockout leads to mitochondrial dysfunction and HF [ 109 ]. In addition, it has been suggested that syntaxin-17 interacts with Drp1 and regulates the calcium concentration in the ER and cytoplasm [ 110 ].…”
Section: Maintenance Of Mitochondrial Ca 2+ Homeosmentioning
confidence: 99%